Adverse Childhood Events and Substance Misuse in Men Who Perpetrated Intimate Partner Violence - Rivas-Rivero, Esther (International journal of offender therapy and comparative criminology, 2022)
Adverse childhood events related to violence suffered have developmental consequences such as the reproduction of such violence in intimate relationships and substance misuse in the later life trajectory. The objective of this study was to analyze the relationship between suffering adverse childhood events and excessive consumption of alcohol and drugs in 120 men, with a mean age of 40.51 years (SD = 11.06), who have abused women in a relationship. The results indicate that those who suffered abuse in childhood and other adverse childhood events in the family of origin consumed alcohol and drugs in excess. Furthermore, the regression models show that alcohol consumption is related to previous substance use by parents, while drug use is related to leaving home due to family conflicts. Also, the consumption of alcohol and other substances is likewise associated with consumption by parents and conflicts within the family. The size of the effect of the relationship increases when different forms of poly-victimization coexist. Conflict treatment is necessary in any setting, especially when it takes place in the family environment and at an early age, to avoid the transmission of maladaptive behaviors associated with substance misuse and violence.